Bias-Based Bullying in California Schools: The Impact of the 2016 Election Cycle - Gill, Monique (Journal of interpersonal violence, 2023)
The purpose of this study is to examine the trends in bias-based bullying between 2013 and 2019 among California youth overall and by type of bias-based bullying and explore the extent to which Trump’s announcement of his candidacy for U.S. President in June 2015 impacted these bullying outcomes. We pooled the student-level survey data from multiple waves of the California Healthy Kids Survey. The final study sample included 2,817,487 middle- and high-school students (48.3% female, 47.9% male, and 3.7% not reported). We examined five specific types of bias-based bullying and any bias-based bullying overall. We employed logistic regression and calculated odds ratios to compare differences in the odds of bias-based bullying before and after Trump announced his candidacy for U.S. President. Between 2013 and 2019, approximately one in four students reported experiencing at least one type of bias-based bullying, based on race, ethnicity, or national origin being the most commonly reported. Trump’s announcement for candidacy was inconsistently associated with differences in the odds of bias-based bullying. Counties in which a higher proportion of the electorate voted for Trump had slightly higher odds of bullying for any bias-based bullying and for all specific types of bias-based bullying. Findings highlight the need for a commitment to protecting students from bullying regardless of their identity. Public health and education researchers and practitioners should draw on our growing understanding of the different dimensions of bullying in designing, implementing, and evaluating intervention approaches that address bias-based bullying, a particularly important cause given the growing polarization in the United States and the increasing salience of identity in the lead-up to and since the 2016 and 2020 elections.